PENINGKATAKAN KINERJA PEGAWAI MELALUI LMX DAN KOMPETENSI DENGAN KOMITMEN ORGANISASIONAL SEBAGAI VARIABEL MEDIASI PADA KANTOR BBPVP SEMARANG - Arne Saputra; Tristijana Rijanti (JURNAL ILMIAH EDUNOMIKA, 2025)
The purpose of this study is to test and analyze the influence of LMX and competence on performance with organizational commitment as a mediator. The sample used was 134 respondents. Testing on the data was carried out using validity and reliability tests. The regression analysis tests used were model tests and hypothesis tests, while the mediation test used the Sobel test. Based on the results of the analysis, it is known that LMX has a positive and significant effect on organizational commitment and performance. Competence affects organizational commitment and performance. Organizational commitment affects performance and mediates the effect of LMX and competence on performance. Keywords: LMX, Competence, Organizational commitment, Performance, BBPVP Semarang.